Men counseling men - Street, John D., 1952- (Eugene, Or. : Harvest House Publishers, 2013)
Under the guidance of John MacArthur, the biblical counseling program at The Master's College has received international acclaim, with instructors who are recognized for their exceptional ability to apply God's truth to real-life problems. Men Counseling Men is an exciting new resource on how to counsel men about the difficulties they face. Written by the school's faculty members, it is an accessible, practical volume that will equip both trained professionals and lay people to provide solidly biblical help for men who are struggling with a variety of major life issues. Readers will learn how they can offer hope and encouragement in relation to depression, parenting, anger, conflict resolution, physical affliction, sexual purity, marital relationships, rebuilding a marriage after adultery. God's Word possesses incredible power. This book will help men experience that power as they turn to the Lord for help. - Publisher.
Foreword / John MacArthur -- Preface / John D. Street -- Part 1 : A man and the Word. Understanding biblical counseling / Joshua Clutterham -- Counseling men with the Bible / John D. Street -- Hope for men in despair / Nathan Busenitz -- Man and the meaning of life / Andrew D. Rogers -- Developing discernment as a counselor of men / Chris Kropf -- Part 2 : A man and his emotions. Men and depression / Robert B. Somerville -- When a man gets angry / Wayne Erick Johnston -- Handling emotional extremes / Mark C. Chin -- Living with severe physical affliction / Jeff Lair -- Contentment for men / Dwight D. Ham -- Part 3 : A man and his relationships. How to develop biblical relationships / S. Andrew Jin -- The husband's role in leaving and cleaving / Charles Mudd -- Parenting young children as a father / Melvin Dirkse -- Parenting adult children as a father / Jim Newheiser -- Godly grandfathers / David Aycock -- Helping men resolve conflict / Ernie Baker -- Part 4 : A man and specific problems. Manhandling idolatrous lust / Nicolas Ellen -- Struggling with homosexuality / Daniel Kirk -- Fathers and teenage homosexuality / Ben Marshall -- When marriage problems become legal problems / Ed Wilde -- Rebuilding a marriage after adultery / Wayne Mack -- Using psychotropic drugs / Geoffrey V. Drew -- Appendices. The gospel for men -- Quick reference guide for men's problems -- Biblical counseling organizations and resources -- The "one another" commands -- About the contributors.
Includes bibliographical references (pages 431-442).
Keywords: Church work with men; Men -- Pastoral counseling of; Pastoral counseling